Flying mouse project - Janis Abols (2014)
A wrist-worn standalone device measuring three principal accelerations along three orthogonal axes, x, y and z, is capable of communicating these values wirelessly to a computer. These acceleration values are sufficient to infer the orientation of the wearer's arm. This forms a facility for the design of a mouse-pointer controlling software based on the inferred hand position and movement. Additionally, a hand gesture performed by the wearer is also described with acceleration values, which are sufficient to distinguish between various different gestures.